PENGARUH PERPUTARAN PIUTANG DAN EFISIENSI MODAL KERJA TERHADAP KEMAMPUAN LABA PADA UNIT PENGELOLAAN KEUANGAN DI BADAN KESWADAYAAN MASYARAKAT DESA PURBAYAN - Endang Masitoh Wahyuningsih, Nanik Sulistiyo Rini (MAJALAH ILMIAH GEMA, 2015)
One of the efforts that utilized it by the Agency Community Self-reliance to improve the welfare of the people in the village is the passing of a way to provide loans to the local community. Expected to be the struggle of the poor in voicing the aspirations and needs of the community and as a driver for poverty reduction is carried out by independent and sustainable society, ranging from the need penentuaan process, decision making, creation, implementation and maintenance program to use. This study aims to determine the effect of the accounts receivable turnover and eficient use of working capital to generate proit in BKM âPurbo Manunggalâ Purbayan Village for 4 years 2009-2012. The ratio used in this study is perputran accounts receivable. While the eficiency of working capital uses Return on Working Capital calculation. On the other hand, BKM âPurbo Manunggalâ especially in the use of Fiscal Management Unit proit calculation capabilities.The method used in this study is a quantitative research method. For data analysis used is multiple regression analysis, the classical assumption test, t test, F test, and the coeficient determinant. Based on this research note that the turnover of receivables and working capital eficiency jointly signiicant effect on the ability of earnings. The results of this study determinant coeficient of 100% proit capability is affected by accounts receivable turnover and working capital eficiency. Keywords: Turnover, Accounts Receivable, Eficiency,Working Capital, AndAbility,Proit.